Near-Infrared Multichannel Filter in a Finite Semiconductor Metamaterial Photonic Crystal - Meng-Ru Wu; Jia-Ren Chang Chien; Chien-Jang Wu; Shoou-Jinn Chang (IEEE Photonics Journal)
A near-infrared (NIR) multichannel filter based on the use of a finite 1-D semiconductor metamaterial (MTM) photonic crystal (PC) is proposed. We consider a PC $\mathrm{air}/(\mathrm{AB})^{N}/\mathrm{air}$ , where $N$ is the stack number, A is a dielectric layer, and B is a semiconductor MTM made of Al-doped ZnO (AZO) and ZnO. Resonant transmission peaks can be found in the frequency region where the permittivity of AZO/ZnO is negative. It is found that the channel number is equal to $N-1$ for a given $N$ and that resonant channels are located in a passband of the photonic band structure. Additionally, the channel positions are tunable, i.e., they can be tuned by the thicknesses of A and B, the filling factor of AZO, and the incidence angle as well. The design of NIR tunable multichannel filter is of technical use for semiconductor optoelectronics.